Switzerland : 2001 Article IV Consultation - Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Authorities of Switzerland. (IMF Staff Country Reports; Country Report ;, 2001)
Switzerland has had a mixed macroeconomic performance over the past quarter century. After stagnating in the 1990s, the Swiss economy has finally shown some spark. Registered unemployment has declined sharply during the upswing and was below 2 percent in early 2001 amidst reports of increasing shortages of skilled labor. The surge in oil prices pushed headline inflation slightly above 1 1\2 percent in 2000, up from 0.8 percent in 1999. The country's longstanding current account surplus reached almost 13 percent of gross domestic product in 2000.